Implementasi Online Learning Pendidikan Pancasila dan Kewarganegaraan Di SMA Negeri 2 Lintau Buo - Nelfisa Fitri; Maria Montesori (Peneliti.net, 2021)
This study aims to analyze the learning process of PPKn through Online learning learning from home at SMA Negeri 2 Lintau Buo. This research is presented in the form of descriptive analysis using case study design. This research was conducted at SMA Negeri 2 Lintau Buo. The informant in this study is a PPKn teacher. The main problem traced in this research is by planning, implementing and resulting during the learning process through online learning. Data collection techniques in this study through observation methods, interviews, and documentation. then analyze the data using interactive models through collecting, reducing, presenting and verifying data. To validate the data is used triangulation of data and data sources. Research shows that learning planning is focused on the implementation of online learning, learning is carried out through several platforms such as google class room and WhatsApp Group. Learning outcomes of 79% above kkm from 32 students. Based on the results of research on PPKn learning through online learning at SMA Negeri 2 Lintau Buo provides implications if learning is not optimal then it is necessary to add supporting facilities and improve teacher competence in utilizing online learning